Carbon Cycle Response to Temperature Overshoot Beyond 2°C: An Analysis of CMIP6 Models. Issue 5 (5th May 2021) - Melnikova, I.; Boucher, O.; Cadule, P.; Ciais, P.; Gasser, T.; Quilcaille, Y.; Shiogama, H.; Tachiiri, K.; Yokohata, T.; Tanaka, K.
Abstract: There is a substantial gap between the current emissions of greenhouse gases and levels required for achieving the 2°C and 1.5°C temperature targets of the Paris Agreement. Understanding the implications of a temperature overshoot is thus an increasingly relevant research topic. Here we explore the carbon cycle feedbacks over land and ocean in the SSP5‐3.4‐OS overshoot scenario by using an ensemble of Coupled Model Intercomparison Project 6 Earth system models. Models show that after the CO2 concentration and air temperature peaks, land and ocean are decreasing carbon sinks from the 2, 040s and become sources for a limited time in the 22nd century. The decrease in the carbon uptake precedes the CO2 concentration peak. The early peak of ocean uptake stems from its dependency on the atmospheric CO2 growth rate. The early peak of the land uptake occurs due to a larger increase in ecosystem respiration than the increase in gross primary production, as well as due to a concomitant increase in land‐use change emissions primarily attributed to the wide implementation of biofuel croplands. The carbon cycle feedback parameters amplify after the CO2 concentration and temperature peaks due to inertia of the Earth system so that land and ocean absorb more carbon per unit change in the atmospheric CO2 change (stronger negative feedback) and lose more carbon per unit temperature change (stronger positive feedback) compared to if the feedbacks stayed unchanged. The increased negative CO2 feedback outperforms the increased positive climate feedback. This feature should be investigated under other scenarios. Plain Language Summary: A large gap between required and currently planned greenhouse gas emission reductions makes possible overshooting the 2°C target of the Paris Agreement before the temperature can return below the target levels. We explore the response of the global carbon cycle to overshoot by analyzing the simulations of state‐of‐art models under an overshoot pathway, where the emissions increase until the 2, 030s and exhibit a steep reduction thereafter. The land and ocean continue to take up carbon from the atmosphere throughout the 21st century, albeit at a reduced rate. The decrease in the ocean carbon uptake occurs before the CO2 concentration peak due to its dependence on the rate of the atmospheric CO2 change, and the decrease in the land uptake occurs due to a stronger increase in the ecosystem respiration than in the photosynthetic carbon absorption and simultaneous large land‐use‐change emissions from the expansion of biofuel crops. After the peaks, land and ocean absorb more carbon from the atmosphere due to higher CO2 concentration and lose more carbon due to warmer temperatures. The influence of higher CO2 concentration wins over the influence of warming, allowing land and ocean to remain carbon sinks till the end of the 21st century. Key Points: After a peak of CO2 growth rate in the SSP5‐3.4‐OS scenario, land and ocean take up carbon for at least 50 years but at a decreasing rate The land sink decrease is due to the larger growth of respiration than photosynthetic production and concurrent land‐use change emissions Under declining emissions, both land and ocean continue to take up carbon at an asymmetrically larger rate